Correlation of amplitude electroencephalography in first 24 h after birth in perinatal asphyxiated neonates with short-term clinical outcome - Goyal, Himanshu; Sharma, Gopikishan; Gulati, R K (Indian Journal of Child Health, 2017)
Objective: To correlate amplitude electroencephalography (aEEG) (in first 24 h after birth) in perinatal asphyxiated neonates with clinical outcome. Materials and Methods: This prospective cohort study was conducted in Jay Kay Lon Mother and Child Hospital, Government Medical College, Kota. All term asphyxiated neonates born with Apgar score of ?7 at 5 min, admitted within 24 h of birth were included in this study. In each case, aEEG was recorded, and neurological examination was done at the time of admission and discharge. Results: Out of 72 cases, 39 neonates of hypoxic-ischemic encephalopathy (HIE) I had normal aEEG. Out of 24 neonates of HIE II, aEEG was normal in 7 and moderately abnormal in 17 neonates. All 9 neonates with HIE III had abnormal aEEG. Sensitivity of aEEG to identify seizures was 76.67%, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 92.86%, 88.46%, and 84.78%, respectively. There were 41 neonates, who were neurologically normal at the time of discharge had normal aEEG. Out of 22 neonates, who were neurologically abnormal at discharge, aEEG was normal in 5 neonates and moderately abnormal in rest 17 neonates. Out of 9 neonates whose death occurred during treatment, aEEG was moderately abnormal in 2 neonates and severely abnormal in 7 neonates. Sensitivity of aEEG (normal pattern) for good outcome was 100% and specificity, PPV, and NPV were 83.87%, 89.13%, and 100%, respectively. Sensitivity of aEEG (abnormal pattern) for poor outcome was 83.87% and specificity, PPV, and NPV were 100%, 100%, and 89.13%, respectively. Conclusion: It is concluded that if aEEG is done within 24 h of birth in asphyxiated neonates, we can predict outcome of the baby. If early aEEG is normal then outcome tends to be favorable. On the other hand, if early aEEG is abnormal, then outcome tends to be unfavorable.